In-vitro Degradation Behaviour of Irradiated Bacterial Cellulose Membrane - D. Darwis; T. Khusniya; L. Hardiningsih; F. Nurlidar; H. Winarno (Atom Indonesia, 2012)
Bacterial cellulose membrane synthesized by Acetobacter xylinum in coconut water medium has potential application for Guided bone Regeneration. However, this membrane may not meet some application requirements due to its low biodegradation properties. In this paper, incorporation of gamma irradiation into the membrane is a developed strategy to increase its biodegradability properties. The in–vitro degradation study in synthetic body fluid (SBF) of the irradiated membrane has been analyzed during periods of 6 months by means of weight loss, mechanical properties and scanning electron microscopy observation compared to that the un-irradiated one. The result showed that weight loss of irradiated membrane with 25 kGy and 50 kGy and immersed in SBF solution for 6 months reached 18% and 25% respectively. While un-irradiated membrane did not give significant weight loss. Tensile strength of membranes decreases with increasing of irradiation dose and further decreases in tensile strength is observed when irradiated membrane was followed by immersion in SBF solution. Microscope electron image of cellulose membranes shows that un-irradiated bacterial cellulose membrane consists of dense ultrafine fibril network structures, while irradiation result in cleavage of fibrils network of cellulose. The fibrils network become loosely after irradiated membrane immersed in SBF solution due to released of small molecular weight carbohydrates formed during by irradiation from the structure. Received: 05 December 2011; Revised: 24 September 2012; Accepted: 29 August 2012